Analisis Strategi Pemasaran Produk Perbankan Syariah di Indonesia - Nur Fajarriah Indah; Nilam Permata Sari; Riska Suainur Sona; Aurelia Agatha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
. Sharia banking in Indonesia is present with the principle of Islamic Shariah. Limited products and services, making sharia banking market share grow slowly. Therefore, a marketing strategy is needed that can increase market share, with a transparent strategy. The aim of this research is to find out how marketing strategies are transparent for sharia banking and what challenges sharia banks face in marketing products. Research methods use descriptive qualitative methods with a legal approach. This is done by using the Law as a basis for analyzing research topics. As a result, a transparent marketing strategy is the main strategy in marketing sharia banking products, asit is in line with the principles of Islamic shariah. Besides, the challenge faced by sharia banking is still a lack of awareness of the Islamic community in the economic sphere. One of them is an abai against the presence of conventional bank interest that is a interest.